The Philosophical Asymmetry of Economic Materialism and the Negation of Goodwill: A Theoretical Review - Angga Pratama; Endang Kartini Panggiarti (Business Finence Analyst Co.,, 2023)
Goodwill is an intangible asset that we can find in a company's accounting cycle. Goodwill is basically subject to depreciation and the measurement related to the amount of depreciation of goodwill does not yet have a strong enough basis so that the assessment of goodwill tends to be subjective and based on management's interests, the impact of this subjective assessment is a failure to present good financial statements and can trigger decision-making errors for third parties. internal or external. The asymmetry of the philosophy of economic materialism is an approach that can be used to repress or negate goodwill by providing an alternative to eliminating goodwill. However, this Philosophical Asymmetry of Economic Materialism is not a final approach because it still depends on several factors that will influence it. Ethical utilitarianism is one of the factors that can influence the effectiveness and implementation of the Philosophical Asymmetry of Economic Materialism as a form of increasing profits and optimizing costs to be incurred by companies in the future. Philosophical asymmetry of Economic Materialism seeks to suppress or negate the existence of goodwill as a form of ethical utilitarianism in the business environment.